Human scavenger protein AIM increases foam cell formation and CD36-mediated oxLDL uptake. Issue 3 (2nd December 2013) - Amézaga, Núria; Sanjurjo, Lucía; Julve, Josep; Aran, Gemma; Pérez-Cabezas, Begoña; Bastos-Amador, Patricia; Armengol, Carolina; Vilella, Ramon; Escolà-Gil, Joan Carles; Blanco-Vaca, Francisco; Borràs, Francesc E; Valledor, Annabel F; et al.
Abstract : Human scavenger protein AIM is involved in macrophage survival, adhesion, and foam cell formation, contributing to atherosclerosis-related mechanisms in the macrophage. ABSTRACT: AIM is expressed by macrophages in response to agonists of the nuclear receptors LXR/RXR. In mice, it acts as an atherogenic factor by protecting macrophages from the apoptotic effects of oxidized lipids. In humans, it is detected in atherosclerotic lesions, but no role related to atherosclerosis has been reported. This study aimed to investigate whether the role of hAIM extends beyond inhibiting oxidized lipid-induced apoptosis. To accomplish this goal, functional analysis with human monocytic THP1 cells and macrophages differentiated from peripheral blood monocytes were performed. It was found that hAIM reduced oxLDL-induced macrophage apoptosis and increased macrophage adhesion to endothelial ICAM-1 by enhancing LFA-1 expression. Furthermore, hAIM increased foam cell formation, as shown by Oil Red O and Nile Red staining, as well as quantification of cholesterol content. This was not a result of decreased reverse cholesterol transport, as hAIM did not affect the efflux significantly from [ 3 H] Cholesterol-laden macrophages driven by plasma, apoA-I, or HDL2 acceptors. Rather, flow cytometry studies indicated that hAIM increased macrophage endocytosis of fluorescent oxLDL, which correlated with an increase in the expression of the oxLDLR CD36. Moreover, hAIM bound to oxLDL in ELISA and enhanced the capacity of HEK-293 cells expressing CD36 to endocytose oxLDL, as studied using immunofluorescence microscopy, suggesting that hAIM serves to facilitate CD36-mediated uptake of oxLDL. Our data represent the first evidence that hAIM is involved in macrophage survival, adhesion, and foam cell formation and suggest a significant contribution to atherosclerosis-related mechanisms in the macrophage.